2005
DOI: 10.1093/hmg/ddi357
|View full text |Cite
|
Sign up to set email alerts
|

No widespread induction of cell death genes occurs in pure motoneurons in an amyotrophic lateral sclerosis mouse model

Abstract: To identify candidate genes that may be involved in motoneuron degeneration, we combined laser capture microdissection with microarray technology. Gene expression in motoneurons was analyzed during the progression of the disease in transgenic SOD1(G93A) mice that develop motoneuron loss. Three major observations were made: first, there was only a small number of genes that were differentially expressed in motoneurons at a pre-symptomatic age (27 out of 34 000 transcripts). Secondly, there is an early specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
111
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(126 citation statements)
references
References 43 publications
14
111
1
Order By: Relevance
“…The significance of these findings is amplified by our analysis of the data from an earlier gene array study (12) with an additional dismutase active SOD1 mutant (SOD1 G93A ). The analysis revealed a 43% overlap (49 genes) with our own dismutase active mutant SOD1 G37R data set, including all our major functional candidate groups (SI Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The significance of these findings is amplified by our analysis of the data from an earlier gene array study (12) with an additional dismutase active SOD1 mutant (SOD1 G93A ). The analysis revealed a 43% overlap (49 genes) with our own dismutase active mutant SOD1 G37R data set, including all our major functional candidate groups (SI Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 95%
“…Because certain aspects of ALS are non-cell autonomous and originate from mutant SOD1 accumulation in non-motor neuronal cells (8,9), cell-type specificity is of high importance when using such an approach. To date, three main gene-expression profiling studies have been reported (10)(11)(12), all of which were restricted to analysis of the adult disease phase in one SOD1 mouse line that accumulates a dismutase active mutant to extraordinarily high levels during disease progression [between 10-and 20-fold over the already abundant endogenous mouse SOD1 (4,13)]. Two studies (10,11) used the entire spinal cord, thus losing cell-type specificity and masking mRNA changes within motor neurons as a consequence of the much more numerous glial cells and their activation before or during disease progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first report described transcriptional analysis of motor neurones isolated from SOD1 G93A mice bred on a mixed background and no differentially expressed genes were detected in the pre-symptomatic mice (Perrin et al 2005). However, in contrast to the whole tissue homogenates, motor neurones did not show activation of apoptotic genes, suggesting that cell death signals derive from other cell types in the spinal cord (Figure 2).…”
Section: Wwwintechopencommentioning
confidence: 97%
“…Several studies have determined the changes in gene expression occurring in motor neurones isolated from the spinal cord of mutant SOD1 G93A mice at different stages during the disease; from the pre-symptomatic stage to paralysis (Ferraiuolo et al 2007;Perrin et al 2005). The first report described transcriptional analysis of motor neurones isolated from SOD1 G93A mice bred on a mixed background and no differentially expressed genes were detected in the pre-symptomatic mice (Perrin et al 2005).…”
Section: Wwwintechopencommentioning
confidence: 99%